Author Correction: Midbrain circuit regulation of individual alcohol drinking behaviors in mice - Barbara Juarez (Nature Portfolio, 2018)
The original version of this Article contained an error in the spelling of the author Scott Edwards, which was incorrectly given as Scott Edward. This has now been corrected in both the PDF and HTML versions of the Article.